Effect of digital health corrective posture exercise program on head and shoulder posture in adolescents: A cluster randomized controlled trial - Baek, Chang-Yoon; Ahn, Jung-Hoon; Lee, Jinyoung; Lee, Hee-Hwa; Lim, Woo-Taek; Park, Hye-Kang; Kim, Hyeong-Dong (Medicine (Baltimore), 2025)
Background: Poor posture, particularly forward head posture and rounded shoulders, has become increasingly prevalent among adolescents due to prolonged screen use and sedentary behaviors. This study aimed to investigate the effects of a 6-week digital health corrective posture exercise (DHCPE) program on head and shoulder posture in adolescents. Methods: A total of 36 subjects were recruited and randomly allocated to 3 groups: the DHCPE group, the face-to-face exercise (FTFE) group, and a control group. The DHCPE and FTFE groups participated in the same corrective posture exercise programs. The DHCPE group conducted the digital health intervention remotely through a monitored screen, while the FTFE group engaged in corrective posture exercises on-site with therapists. Each intervention lasted 50 minutes and was conducted 3 times a week over a period of 6 weeks for both groups. The outcome measurements included protracted head and shoulder distances, trunk lean (the angle of shoulder inclination relative to the pelvis), trunk deviation, shoulder and pelvic height levels, and the absolute differences and inequality ratios between both sides. All assessments were conducted both preintervention and postintervention. Results: Both the DHCPE and FTFE groups demonstrated significant improvements in protracted head, left protracted shoulder, and trunk lean following the intervention. The interaction effect revealed that both the DHCPE and FTFE groups exhibited significant improvements in these measurements compared with the control group. Furthermore, no significant differences were found between the improvements observed in the DHCPE group and those in the FTFE group. Conclusion: DHCPE and FTFE were effective in improving head and shoulder posture in adolescents. The improvements in the DHCPE group were comparable to those achieved in the FTFE group. DHCPE has the potential to serve as a viable alternative to FTFE for enhancing head and shoulder posture in this population.